2014
DOI: 10.1002/cbic.201402100
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Scaffolded Multivalent Ligands to Modulate Cell Function

Abstract: We report a simple, versatile, multivalent ligand system that is capable of specifically and efficiently modulating cell‐surface receptor clustering and function. The multivalent ligand is made of a polymeric DNA scaffold decorated with biorecognition ligands (i.e., antibodies) to interrogate and modulate cell receptor signaling and function. Using CD20 clustering‐mediated apoptosis in B‐cell cancer cells as a model system, we demonstrated that our multivalent ligand is significantly more effective at inducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 43 publications
0
47
0
Order By: Relevance
“…, polypeptides, 116 poly-DNA 17 ). Mobility and biodistribution of carriers should be characterized.…”
Section: Conclusion and Beyondmentioning
confidence: 99%
“…, polypeptides, 116 poly-DNA 17 ). Mobility and biodistribution of carriers should be characterized.…”
Section: Conclusion and Beyondmentioning
confidence: 99%
“…This was likely due to multivalency of the P-MORF2 conjugate (8 binding sites per chain) in comparison to the divalent mAb. Our lab [10, 11] and others [12, 13] have previously shown that the multivalency of anti-CD20 constructs can increase binding affinity and apoptosis-inducing efficiency by several fold, when compared to their monovalent or divalent counterparts. We have also reported that, in addition to valence, the polymer length ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Lately, a variety of self-assembled and biofunctionalized polymer domains have now been used to successfully regulate signaling networks [13]. In future, the design of potent multivalent conjugates that can organize cell receptors into nanoscale clusters and control cell fate will further impact this research field [1,14,15].…”
Section: Molecular Nanopatterns For Controlling Transmembrane Clusteringmentioning
confidence: 99%